Multi-Criteria Decision-Making The Selection of IoT-Based Inverter Smart Grid System and Smart Meter for Solar Photovoltaic and Wind Turbine Installations in Pelabuhan Ratu CFPP using AHP & TOPSIS Method - Prayogo, Bobby; Yudisaputro, Hendra (Department of Mechanical and Industrial Engineering, 2024)
The selection of appropriate inverters is pivotal in maximizing the efficiency and performance of solar photovoltaic (PV) and wind turbine systems, as they directly impact the overall energy conversion efficiency and system output by influencing efficiency and reliability. Inverter selection also encompasses critical criteria like cost, compatibility with renewable energy sources, and environmental considerations. Thus, an exhaustive and systematic approach is essential to effectively evaluate and compare different inverter options. This study employs multi- criteria decision-making to address these challenges, evaluating the identified criteria using the Analytical Hierarchy Process (AHP) and ranking them to determine the optimal solution via Technique for Order of Preference by Similarity to the Ideal Solution (TOPSIS). Consequently, the investigation identifies smart grid and smart meter inverters as the ideal solutions, successfully addressing concerns regarding power stability, communication and connectivity, security, data management, and cost. The proposed methodology yields a substantial total equity portion of USD 9,325.71, accompanied by impressive earnings before interest, taxes, depreciation, and amortization (EBITDA) of USD 1,734.09 per year. The estimated payback period is 6.85 years, and the return on investment (ROI) reaches a remarkable 338.07%. Additionally, the net income significantly reduces the production cost, with USD 40,853.34 in a single period.